Insights on the virulence of swine respiratory tract mycoplasmas through genome-scale metabolic modeling. (December 2016) - Ferrarini, Mariana; Siqueira, Franciele; Mucha, Scheila; Palama, Tony; Jobard, Élodie; Elena-Herrmann, Bénédicte; R. Vasconcelos, Ana; Tardy, Florence; Schrank, Irene; Zaha, Arnaldo; Sagot, Marie-France
Abstract Background The respiratory tract of swine is colonized by several bacteria among which are threeMycoplasma species:Mycoplasma flocculare, Mycoplasma hyopneumoniae andMycoplasma hyorhinis . While colonization byM. flocculare is virtually asymptomatic, M. hyopneumoniae is the causative agent of enzootic pneumonia andM. hyorhinis is present in cases of pneumonia, polyserositis and arthritis. The genomic resemblance among these threeMycoplasma species combined with their different levels of pathogenicity is an indication that they have unknown mechanisms of virulence and differential expression, as for most mycoplasmas. Methods In this work, we performed whole-genome metabolic network reconstructions for these three mycoplasmas. Cultivation tests and metabolomic experiments through nuclear magnetic resonance spectroscopy (NMR) were also performed to acquire experimental data and further refine the models reconstructedin silico . Results Even though the refined models have similar metabolic capabilities, interesting differences include a wider range of carbohydrate uptake inM. hyorhinis, which in turn may also explain why this species is a widely contaminant in cell cultures. In addition, the myo-inositol catabolism is exclusive toM. hyopneumoniae and may be an important trait for virulence. However, the most important difference seems to be related to glycerol conversion to dihydroxyacetone-phosphate, which produces toxic hydrogen peroxide. This activity, missing only inM. flocculare, may be directly involved in cytotoxicity, as already described for two lung pathogenic mycoplasmas, namelyMycoplasma pneumoniae in human andMycoplasma mycoides subsp.mycoides in ruminants. Metabolomic data suggest that even though these mycoplasmas are extremely similar in terms of genome and metabolism, distinct products and reaction rates may be the result of differential expression throughout the species. Conclusions We were able to infer from the reconstructed networks that the lack of pathogenicity ofM. flocculare if compared to the highly pathogenicM. hyopneumoniae may be related to its incapacity to produce cytotoxic hydrogen peroxide. Moreover, the ability ofM. hyorhinis to grow in diverse sites and even in different hosts may be a reflection of its enhanced and wider carbohydrate uptake. Altogether, the metabolic differences highlightedin silico and in vitro provide important insights to the different levels of pathogenicity observed in each of the studied species.